Age at menarche and the risk of operative delivery. (1st February 2019) - Chong, Hsu Phern; Frøen, J. Frederik; Richardson, Sylvia; Liquet, Benoit; Charnock-Jones, D. Stephen; Smith, Gordon C. S.
Abstract: Objectives: We sought to evaluate the impact of later menarche on the risk of operative delivery. Population: We studied 38, 069 eligible women (first labors at term with a singleton infant in a cephalic presentation) from the Norwegian Mothers and Child Cohort Study. The main exposures were the age at menarche and the duration of the interval between menarche and the first birth. Methods: Poisson's regression with a robust variance estimator. Main outcome measures: Operative delivery, defined as emergency cesarean or assisted vaginal delivery (ventouse extraction or forceps). Results: A 5 year increase in age at menarche was associated with a reduced risk of operative delivery (risk ratio [RR] 0.84, 95%CI 0.78, 0.89; p  < .001). Adjustment for the age at first birth slightly strengthened the association (RR 0.79, 95%CI 0.74, 0.84; p  < .001). However, the association was lost following adjustment for the menarche to birth interval (RR 0.99, 95%CI 0.93, 1.06; p  = .81). A 5 years increase in menarche to birth interval was associated with an increased risk of operative delivery (RR 1.26, 95%CI 1.23, 1.28; p  < .001). This was not materially affected by adjustment for an extensive series of maternal characteristics (RR 1.23, 95%CI 1.20, 1.25; p  < .001). Conclusions: Later menarche reduces the risk of an operative first birth through shortening the menarche to birth interval. This observation is consistent with the hypothesis that the pattern and/or duration of prepregnancy exposure of the uterus to estrogen and progesterone contributes to uterine aging.